Experimental investigation and performance analysis of Archimedes screw generator. Issue 2 (3rd March 2016) - Dellinger, Guilhem; Terfous, Abdelali; Garambois, Pierre-Andre; Ghenaim, Abdellah
ABSTRACT: The generation of renewable energy with Archimedes screw generators (ASG) transforming potential energy of fluid flow into mechanical energy is a growing technology suitable for low-head hydraulic sites. This paper presents an improved theoretical model linking screw performance to screw geometry and flow conditions. This model takes into account leakages, friction losses and variable fill levels. The modelled values of torques and efficiencies are in a fairly good agreement with experimental results obtained for a laboratory-scale screw. The downstream screw immersion is shown to impact ASG efficiency and an optimal immersion level is proposed. It has been found that fluid friction on the screw is not negligible. The analysis shows that a single value of the friction coefficient is suitable for modelling the screw performance under various flow conditions. The leakage phenomenon at under-filling flow conditions and friction forces in complex turbulent flows need to be further studied.